Quantum Mechanics as Structuralist Chimera (London Journal of Research In Humanities and Social Sciences, 2025)
I argue that properties and relations are in the same boat with respect to quantum mechanics. That just as properties cannot be considered as ``hidden variables" so also neither can the relation of being correlated with. Nevertheless properties and relations can both be understood as incomplete expressions: they are both contextual, properly understood. The argument on this leverages a neglected proof by Adn Cabello. We show that this latter argument extends and strengthens an argument given by van Fraassen in his (2006). The argument given also considerably strengthens the arguments given previously by Cao (2003) and Psillos (2006). I end by sketching a way of understanding that this contextuality is similar across relativity theory and quantum theory.
Keywords: Gender; propensity score matching; Youth; Chile; NEET; poverty household